CCR2-Dependent Recruitment of Tregs and Monocytes Following Radiotherapy Is Associated with TNFα-Mediated Resistance - Mondini, Michele; Loyher, Pierre-Louis; Hamon, Pauline; Gerbé de Thoré, Marine; Laviron, Marie; Berthelot, Kevin; Clémenson, Céline; Salomon, Benoit L; Combadière, Christophe; Deutsch, Eric; Boissonnas, Alexandre (Cancer immunology research, 2019)
Radiotherapy (RT) represents one of the main anticancer approaches for the treatment of solid tumors. Beyond the expected direct effects of RT on tumor cells, evidence supporting the importance of an immune response to RT is growing. The balance between RT-mediated immunogenic and tolerogenic activity is ill-defined and deserves more attention. Herein, a murine model of head and neck squamous cell carcinoma was used to demonstrate that RT upregulated CCL2 chemokine production in tumor cells, leading to a CCR2-dependent accumulation of tumor necrosis factor alpha (TNFα)-producing monocytes and CCR2 regulatory T cells (Treg). This corecruitment was associated with a TNFα-dependent activation of Tregs, dampening the efficacy of RT. Our results highlight an unexpected cross-talk between innate and adaptive immune system components and indicate CCL2/CCR2 and TNFα as potential clinical candidates to counterbalance the radioprotective action of monocyte-derived cells and Tregs, paving the way for potent combined radioimmunotherapies.